Arbuscular mycorrhizal symbiosis ameliorates the optimum quantum yield of photosystem II and reduces non-photochemical quenching in rice plants subjected to salt stress - Porcel, Rosa (Journal of plant physiology, 2015)
Copyright © 2015 Elsevier GmbH. All rights reserved.